A water-stable terbium metal–organic framework with functionalized ligands for the detection of Fe3+ and Cr2O72− ions in water and picric acid in seawater. Issue 21 (15th May 2020) - Yu, Hai-Huan; Chi, Jia-Qi; Su, Zhong-Min; Li, Xiao; Sun, Jing; Zhou, Chen; Hu, Xiao-Li; Liu, Qun
Abstract : A novel Tb-MOF-A was fabricated by functionalized ligands and Tb 3+, which displays high fluorescence, water stability up to 21 days and rapid, cyclic, simultaneous detection of Fe 3+, Cr2 O7 2− ions in water and picric acid in seawater. Abstract : The existence of Cr2 O7 2− anions and excessive Fe 3+ cations in water and picric acid in seawater causes irreversible harm to human health and aquatic organisms. Herein, a water-stable terbium metal–organic framework (namely Tb-MOF-A ) was fabricated from 1, 10-phenanthroline (phen) and 2, 3, 5, 6-tetrafluoroterephthalic acid (H2 tftba) under hydrothermal conditions. Due to the features of the pyridine- and fluorine-functionalized organic ligands and Tb 3+ ions, Tb-MOF-A can quickly, quantitatively and circularly detect Cr2 O7 2− anions and Fe 3+ cations in a water environment and picric acid in a simulated seawater environment. In addition, the stability studies exhibit excellent water stability and fluorescent stability for 21 days, thermal stability and fluorescent stability in water (−18 °C to 50 °C), and acid-basic solution stability and fluorescent stability (pH = 2–11) for 4 days. Novel Tb-MOF-A is expected to be applied in practical water environment engineering as an excellent sensor with high water-stability, sensitivity, and reusability.